THE IMPLEMENTATION OF EXTENSIVE READING TO IMPROVE STUDENT’S READING SKILLS (Experimental Study on Class X Students of SMA Negeri 5 Simeulue Barat) - Saleh, Arsan; Muchsin, Muchsin; Faudi, Faudi (Jurnal Seramoe Education, 2024)
This research aims to determine significant differences in improving reading skills between students who are taught using extensive reading compared to students who do not use extensive reading in Class X SMA Negeri 5 West Simeulue. This type of research uses a quantitative approach, with ‎ The total population is 46 students who will be the sample consisting of 22 students of class and the independent variable (X) is The Implementation ‎of Extensive Reading to improve students’ reading skills. The data collection technique in this research is in the form of Pre-test and Posttest and analyzing the data using the T-score formula. The results of this research show the average value of students Class After the author provided treatment, the average score of students in the experimental group was 88.17. ‎It can be concluded that the students’ reading skills before being given treatment were ‎‎37.79 and were still in the low category. Class X students at SMA Negeri 5 West Simeulue are interested in Implementation ‎extensive reading. Students use the time to do extensive reading. It was proven that their ability in reading skills increased by 50.38 points. So there has been an increase in the reading ability of Class X SMA Negeri 5 ‎Simeulue students. and There is a significant difference in improving reading skills among Class This is proven by the results of the research where the post test t score for both groups was 68.21. Meanwhile, the t table for degrees of freedom 48-2= 46 is 2.00. Thus, the t-score (68.21) is higher than the t-table (2.00).